Mens sana in corpore sano: compreensões de corpo, saúde e educação - Mendes, Maria Isabel Brandão de Souza (2005)
This thesis proposes that the idea expressed in Juvenal s quotation Mens Sana in Corpore Sano, produced in the Ancient Greek-Roman civilization includes undestandings of body, heath and education that were reapropriated and reorganized by scientific and pedagogical theories in the XIX and XX centuries. These theories, especially the ones that received contributions from the biomedical sciences, have influenced Physical Education in the search of becoming a science. In order to realize this reapropriation, we have analyzed the transformations in the concepts of body, health and education produced in the area discourse, aiming at pointing out elements to the configuration of a theory that is being called Corpore Sano. The theory constitutes in possible systematization of scientific, philosophical and pedagogical concepts, and as such, an understanding of the scientific fundaments of Physical Education. The corpus of this analysis was composed by 148 articles that were published in Revista Brasileira de Ciências do Esporte digitalized in the period between 1979 and 2003 and selected according to theme: body, biology, physical activity, effort physiology and health. The analysis of the content and the referential interpretation allowed the combination of philosophical reflection with attention to the empiric field as a comprehensive dimension. Based on the corpus of the analysis it is possible to configure meta-arguments about the concepts of body, health and education in the scientific production of Physical Education. As a metaresearch. Our study did not intend to judge the analyzed production, but look for theoretical elements that may generate a reflection about the scientific rationality in Physical Education and developments in the pedagogical field and in body practices. Such a reflection might be recognized as a theory of the living body, susceptible to modifications and interrogations that are proper of knowledge and practices of Physical Education. It is a theory rejects the idea of the complete truth and holds the comprehension that the truth is built historically through relations among different kinds of knowledge and Physical Education practices